The Role of Religiosity in Shaping Self-Concept among University Students with Divorced Parents - Khansa, Shofia; Hanan Zahara, Fidia; Endi, Endi (Asosiasi Psikologi Islam (API) Himpsi, 2023)
The phenomenon of divorce inWest Java, the highest in Indonesia, serves as the backdrop for this study, which examines its impact on children, particularly in their adulthood. This research aims to analyze the effect of religiosity on self-concept among college students aged 18-25 years from divorced families in West Java. Data were collected from 245 students through an online survey using a validated and reliable questionnaire. The normality test confirmed that the data were normally distributed (Asymp. Sig. = 0.136, p > 0.05) and linearuty test indicated a linear relatonship between religiosity and self-concept (p > 0.05). Additionally, the heteroscedasticity test showed no symptoms of heteroscedasticity (p > 0.05). A simple linear regression analysis was conducted to test the research hypothesis. The result show that religiosity has a statistically significant effect on self-concept, with a coefficient of determination (R²) of 2.7%. indicating that religiosity contributes minimally to self-concept. The regression model yielded an F-value of 6.838 (p < 0.05), confirming the significance of the relationship. However, 97.3% of the variation in self-concept is influenced by other factors. These findings highlight the limited but notable role of religiosity in shaping self-concept among students with divorced parents.